SLEEP DISTURBANCES AND DEPRESSION: DIRECTIONS AND MECHANISAMS OF INTERACTION - Grubač, Željko Z; Jovanović, Đurđa; Puškaš, Nela; Hrnčić, Dragan (Medicinski podmladak, 2018)
Sleep represents physiological process which effects are crucial to maintain homeostasis.  Sleep disturbances are widely spread within the population worldwide. The loss in quantity or quality of sleep is associated with numerous diseases. Also, sleep disturbances are highly connected to depressive disorders, but exact mechanism of this interaction still remain unknown. Understanding the underlying mechanisms could be the key for treatment of both disorders especially in patients with psychosomatic and psychiatric comorbidities. Therefore, we will summarize the most recent findings on the connection between sleep disturbances and depressive disorders in this article including the mechanisms of this interaction. key words: sleep, depression, sleep interruption, BDNF